2011
DOI: 10.1021/om101125g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Decarbonylation Reactions of Diiron Cyclopentadienyl Complexes with Bent-Phosphinidene Bridges

Abstract: The phosphinidene complexes [Fe2Cp2(μ-PR)(μ-CO)(CO)2] (Cp = η5-C5H5; R=Cy, Ph, Mes, Mes*; Mes = 2,4,6-C6H2Me3, Mes* = 2,4,6-C6H2 t Bu3) were readily prepared in high yields through a two-step procedure starting from the corresponding phosphine complexes [Fe2Cp2(μ-CO)2(CO)(PH2R)]. When R = Cy, Ph, Mes, the first step required the oxidation of the phosphine complex with 1 equiv of [FeCp2]BF4, this being followed by spontaneous dehydrogenation to yield the cationic phosphide complexes [Fe2Cp2(μ-PHR)(μ-CO)(CO)2]B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 91 publications
0
18
0
Order By: Relevance
“…In particular, by using density functional theory (DFT) methods (see the Experimental Section), we have searched for isomers having either a pyramidal bridging ligand of type C or a bent terminal phosphinidene ligand. The reason for this is that recent work on the diiron complex [Fe 2 Cp 2 (PR*)­(CO) 3 ] revealed that such alternative structures were of similar energy, with the one having the bent terminal PR* group remarkably reacting with H 2 under mild conditions (4 atm, 293 K), while possibly being also behind a C–H bond cleavage in the PR* ligand analogous to the one required to yield complexes 3 . Our search on the potential energy surface of our Mo 2 system actually failed to find a structure with a significantly pyramidalized bridging ligand of type C , but we found a minimum with a terminal and significantly bent phosphinidene ligand ( 1T , Mo–P–C ca.…”
Section: Resultsmentioning
confidence: 80%
“…In particular, by using density functional theory (DFT) methods (see the Experimental Section), we have searched for isomers having either a pyramidal bridging ligand of type C or a bent terminal phosphinidene ligand. The reason for this is that recent work on the diiron complex [Fe 2 Cp 2 (PR*)­(CO) 3 ] revealed that such alternative structures were of similar energy, with the one having the bent terminal PR* group remarkably reacting with H 2 under mild conditions (4 atm, 293 K), while possibly being also behind a C–H bond cleavage in the PR* ligand analogous to the one required to yield complexes 3 . Our search on the potential energy surface of our Mo 2 system actually failed to find a structure with a significantly pyramidalized bridging ligand of type C , but we found a minimum with a terminal and significantly bent phosphinidene ligand ( 1T , Mo–P–C ca.…”
Section: Resultsmentioning
confidence: 80%
“…4 atm). While the cyclohexylphosphinidene complex 1a failed to react after 6 d in toluene solution, we found that the more congested compound 1c did react with H 2 under the same conditions, the reaction being completed in about 16 h, to give the phosphine complex [Fe 2 Cp 2 (μ-CO) 2 (CO)(PH 2 Mes*)] (actually, the synthetic precursor of 1c ) as the major compound (ca. 50% by 1 H NMR).…”
Section: Resultsmentioning
confidence: 87%
“…50% by 1 H NMR). Other products detected in the reaction mixture were free phosphine PH 2 Mes* (20%), the dimer [Fe 2 Cp 2 (CO) 4 ] (15%), the oxophosphinidene complex [Fe 2 Cp 2 (CO) 3 {P(O)Mes*}] (10%), and the phosphindole derivative [Fe 2 Cp 2 (μ-CO) 2 (CO){PH(CH 2 CMe 2 )C 6 H 2 t Bu 2 }] (5%). The presence of all these minor products can be rationalized by taking into account the known degradation processes of 1c in solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…120 ppm), stronger than anticipated. For instance, the 31 P chemical shifts of trigonal and pyramidal phosphinidene ligands in the iron complexes [Fe 3 Cp 3 (μ-PMes)­(μ-PHMes)­(μ-CO) 2 (CO)] and [Fe 2 Cp 2 (μ-PMes)­(μ-CO)­(CO) 2 ] differ by some 250 ppm …”
Section: Resultsmentioning
confidence: 99%